Soft skills and knowledge required for a professional accountant: Evidence from Jordan - Sally Abu Asabeh (17944931) (2023)
Due to the rapidly changing economic environment, increasing competition, and the pervasive influence of new technologies in businesses, the accounting profession is encountering challenges in adapting to these changes. Accountants worldwide face new market demands, leading to numerous organizations and individuals in many countries advocating for modifications in accounting curricula to equip students with the necessary skills and knowledge. This quantitative study aims to assess the soft skills possessed by Jordanian accounting graduates and evaluate their adequacy in meeting employer expectations, as employers play a crucial role in enhancing employability. It also investigates the extent to which accounting graduates perceive their university programs to have promoted soft skills and knowledge. A total of 101 students, 75 professionals, and 54 academics participated in the online questionnaire. The participants were asked to assess the importance of 45 skills, categorized into five groups: interpersonal and communication skills, intellectual skills, personal skills, technical and functional skills, and organizational skills/business management skills. The study uncovered disparities between students’ perceptions of skill importance and the perceptions of academics and employers. Moreover, the study’s findings align with existing literature, indicating that employers and academics emphasize interpersonal and communication skills, while graduates prioritize technical and functional skills. Other Information Published in: Cogent Education License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/2331186x.2023.2254157